Contemporary Management of Acute Type B Dissection. Issue 3 (March 2016) - Scott, A.J.; Bicknell, C.D.
Abstract : Objective: Growing confidence in thoracic endovascular aortic repair (TEVAR) for the management of acute type B aortic dissection has resulted in controversies regarding optimum patient selection and the timing of intervention. In this review a clinical vignette to present a practical perspective on the contemporary management of acute type B dissection (ABAD) in a specialist vascular centre with particular focus on areas of debate is used. Methods: This is a narrative clinical review. Results: Aggressive anti-impulse therapy is the cornerstone of management of all patients with ABAD. However, 20–30% of patients develop complicated ABAD defined by the presence of malperfusion syndromes, acute aortic dilatation, dissection extension, or persistent pain and hypotension. These complicated patients typically require intervention, and non-randomised series suggest TEVAR to be an effective alternative to open repair with a lower morbidity. There is considerable interest and controversy surrounding the use of TEVAR in uncomplicated ABAD patients for whom the intervention-free survival at 6 years is less than 50% for patients managed with anti-impulse therapy. Data regarding this question are sparse, but two randomised trials (ADSORB and INSTEAD) both demonstrated a higher rate of favourable aortic remodelling in patients managed with TEVAR than medical therapy alone. However, it is unclear whether this positive remodelling translates into a reduction in long-term mortality sufficient to balance the early perioperative hazards of endografting. Conclusion: Despite increasing adeptness at endovascular stenting, the long-term outcomes of patients with ABAD leave significant room for improvement. In particular, the optimum management of patients with uncomplicated disease is unclear and guidance from trials powered for long-term mortality is awaited. Until then, the principals of management of ABAD remain aggressive medical therapy for all patients, with TEVAR primarily reserved for those who develop complications.